2018
DOI: 10.1111/1462-2920.14492
|View full text |Cite
|
Sign up to set email alerts
|

A low proportion of rare bacterial taxa responds to abiotic changes compared with dominant taxa

Abstract: Summary In many studies, rare bacterial taxa have been found to increase in response to environmental changes. These changes have been proposed to contribute to the insurance of ecosystem functions. However, it has not been systematically tested if rare taxa are more likely to increase in abundance than dominant taxa. Here, we study whether rare soil bacterial taxa are more likely to respond to environmental disturbances and if rare taxa are more opportunistic than dominant taxa. To test this, we applied nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 46 publications
5
42
1
Order By: Relevance
“…For instance, local physicochemical properties have greater effects on community compositions of both rare and abundant bacteria compared to geospatial factors (Ji et al, 2020). However, most studies investigate the biogeography of rare and abundant bacterial communities in agricultural soils (Kurm et al, 2019; Hou et al, 2020; Jiao & Lu, 2020a; Liang et al, 2020), and little is known about environmental adaptation and community assembly processes of rare and abundant bacterial and fungal taxa in natural wetlands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, local physicochemical properties have greater effects on community compositions of both rare and abundant bacteria compared to geospatial factors (Ji et al, 2020). However, most studies investigate the biogeography of rare and abundant bacterial communities in agricultural soils (Kurm et al, 2019; Hou et al, 2020; Jiao & Lu, 2020a; Liang et al, 2020), and little is known about environmental adaptation and community assembly processes of rare and abundant bacterial and fungal taxa in natural wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundance of a rare or abundant taxon is the result of a tradeoff between its growth and death rates (Ratzke et al, 2018). Rare and abundant microbial taxa show diverse responses to environmental change (Kurm et al, 2019; Liang et al, 2020). Environmental thresholds of species reveal changes in taxa distributions along an environmental gradient over space or time (Baker & King, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, co-occurrence analyses have unraveled that microbes do not prosper as individual units, but rather as complex connected and interactive networks [2]. Such analyses hold special importance to understand how microbe-microbe associations modulate the plant responses to the changing environmental factors [3][4][5]. Omic studies have suggested that certain keystone taxa or key phylotypes govern the networking interactions between community members, expanding our knowledge about how microbes adapt to the plant's environmental pressures [6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, local physicochemical properties have greater effects on both rare and abundant bacterial β-diversity compared to geospatial factors [20]. However, most studies investigate the biogeography of rare and abundant bacterial communities in agricultural soils [17,22,24,25], and little is known about rare and abundant bacterial and fungal taxa in natural wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundance of a rare or abundant taxon is the result of a tradeoff between its growth and death rates [29]. Rare and abundant microbial taxa show diverse responses to environmental change [22,25]. Environmental thresholds of arbuscular mycorrhizal fungi in European grassland are estimated using the accumulated values of change points of all the species in a given microbial community [30].…”
Section: Introductionmentioning
confidence: 99%